2012
DOI: 10.1158/2159-8290.cd-11-0315
|View full text |Cite
|
Sign up to set email alerts
|

Cancers of the Colon and Rectum: Identical or Fraternal Twins?

Abstract: summary: Colorectal cancer represents a major cause of cancer morbidity and mortality, with approximately 1.2 million cases and 600,000 deaths worldwide each year. Because of the anatomic continuity of the colon into the rectum, cancers affecting these organs have historically been considered equivalent. In this Prospective, we discuss the clinical and experimental data suggesting that colon cancer and rectal cancer are highly related, but distinct, diseases. Reconsidering the relationship between these cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 22 publications
0
51
1
4
Order By: Relevance
“…Supporting this concept, the frequency of pulmonary metastases was increased in patients of our cohort with rectal cancer. Here, tumors partly drain through the inferior rectal vein to the vena cava, potentially promoting hematogenous dissemination in the lungs [14].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this concept, the frequency of pulmonary metastases was increased in patients of our cohort with rectal cancer. Here, tumors partly drain through the inferior rectal vein to the vena cava, potentially promoting hematogenous dissemination in the lungs [14].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, and consistently with the hypothesis of ADCC as an important mechanism of action of cetuximab against micrometastases, we found that carriers of 131R and/or 158F alleles had a significantly lower risk of distant failure than patients homozygous for 131H and/or 158V when cetuximab was added to the study sequential treatment. It is worth noting that additional signaling pathways beyond EGFR (i.e., IGF-1R pathway) which have been shown to cross-talk with EGFR downstream effectors and mediate the ADCC-independent therapeutic effects of cetuximab are more frequently activated and potentially more clinically relevant in rectal cancer than in colon cancer (36)(37)(38). Therefore, our findings could be potentially influenced by the specific location of the primary tumor and may not apply to a population of patients with colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating this SNP were either restricted to patients with colon cancer or conducted in unselected CRC populations [7,[9][10][11][12][13][14][15][16]. However, differences exist between colon and rectal cancers with regards to tumour biology and treatment approach including frequency of microsatellite instability and BRAF mutation, prognostic relevance of KRAS mutation, miRNA expression profile and routine use of radiotherapy in LARC [21].…”
Section: Discussionmentioning
confidence: 99%